LEGAL RECONSTRUCTION OF INTELLECTUAL PROPERTY RIGHTS PROTECTION BASED ON DIGITAL JUSTICE TOWARDS PLATFORM ECONOMIC INEQUALITY IN INDONESIA - Muhibuddin; Zulkifli; Teuku Yudi Afrizal; Nasrianti; Sofyan Jafar (PT. Radja Intercontinental Publishing, 2025)
Indonesia’s digital economy exceeded USD 82 billion in transaction value in 2023 and is projected to become the largest digital market in Southeast Asia by 2030. Despite this rapid growth, the expansion of platform-based digital markets has generated significant economic inequality between digital platforms and intellectual property rights (IPR) holders, particularly local creators and small digital enterprises. This study analyzes the legal reconstruction of intellectual property protection based on the principle of digital justice in addressing platform economic inequality in Indonesia. Employing a normative juridical method, the research applies statutory, conceptual, and comparative approaches. The study finds that Indonesia’s existing IPR framework remains largely conventional and has not adequately responded to challenges arising from algorithmic control, data monopolization, unequal royalty distribution, and the dominance of digital platforms within the digital economy ecosystem. Furthermore, the lack of algorithmic transparency and limited legal accountability of digital platforms contribute to structural imbalances in the distribution of digital economic benefits. This study proposes a legal reconstruction model through strengthening platform accountability, reforming digital royalty mechanisms, enhancing protection of creators’ digital rights, and harmonizing IPR regulations with digital economy and data protection laws. The study concludes that intellectual property protection in the digital era should not solely emphasize legal certainty, but must also ensure distributive digital justice and equitable economic participation in Indonesia’s platform economy.